Pengaruh Struktur Aktiva dan Profitabilitas Terhadap Harga Saham - Muhammad Rivandi; Lasmidar Lasmidar (Fakultas Sastra Universitas Ekasakti, 2021)
The stock price interpreted as the price formed from the interaction between the seller and the buyer of shares which is motivated by the expectation of company profits. This study aims to determine and analyze the effect of asset structure and profitability on stock prices. The data processed is secondary data from the annual reports of 11 food and beverage sub-sector manufacturing companies listed on the IDX in 2015-2019 which were taken through purposive sampling. The method used in this research is panel data regression analysis method using Eviews version 8.0. The results of this study indicate that: asset structure and profitability have a positive effect on stock prices